Evaluating the Effectiveness of a Virtual Reality Aquaponic Greenhouse Tour as an Educational Tool for Enhancing Food Safety Knowledge - Cándido M., Stephany M. (Universidad Zamorano, 2025)
Food safety (FS) is a global public health concern that requires innovative approaches to improve knowledge and practice. Virtual Reality (VR) has emerged as a promising tool for immersive and effective training. The objective of this study was to evaluate the effectiveness of a VR Aquaponic Greenhouse Tour for enhancing knowledge of (FS) and aquaponics. This project was conducted in two phases: at Purdue University (I), and Zamorano University (II) using VR headsets and laptop-based tours. Descriptive and explanatory statistics were applied to evaluate quiz performance and survey responses. A Mann-Whitney U test compared quiz performance by gender (I), and a t-test assessed differences before and after the tour (II), both at a 95% confidence level (p ≤ 0.05). Descriptive analysis summarized demographic data and participants’ perceptions through Likert-scale responses. Findings revealed that the VR tour significantly improved participants' knowledge, with quiz scores showing a statistically significant increase after the tour in all groups regardless of gender and majors. The study also found that the tour increased participants' interest in both FS and aquaponics. Most participants considered VR experience an effective learning tool and a viable alternative to in-person farm tours. The study concluded that VR-based tours were an effective way to teach FS and aquaponics in a format that is practical and accessible, allowing more people to benefit from this training without being limited by distance or physical constraints. These insights contribute to understanding innovative educational technologies and provide recommendations for educators and stakeholders in food and agricultural systems.
Keywords: Digital simulation; educational technology; immersive environment; safe food handling; sustainable farming system